Exploring The Role Of Thyroid Hormone Levels In Gallstones In Jordan: A Reasearch Study - As’ad M.D, Anas; Al-Shbailat M.D, Samer A; Alqarqaz M.D, Eyad; Alwreikat M.D , Tareq; Alananzh, Mohammad (Journal of Neonatal Surgery, 2025)
Background: Cholesterol, bilirubin, or a mixture of both gallstones are hardened deposits that develop in the gallbladder and bile ducts. When there is excessive cholesterol, bile salts, and bilirubin among other substances present in bile, it can result into the formation of gallstones. Gallstones are well known to be one of the most common reasons for hospital admissions, which strikes suspicion towards thyroid imbalance of some sort. The reason this seems logical is that Hypothyroidism affects so many people across the globe coupled with its impact on hepatic lipid homeostasis as well as biliary secretion and gallbladder motility all some of the things thought to contribute into cholesterol gallstone disease. Aim;To investigate between the association between thyroid hormone levels and the risk of Gallstones in Jordan. Materials and Methods: The purpose of this cross-sectional study is to investigate the relationship between thyroid hormone levels and gallstone development. From July 2023 to March 2025, information was gathered from Al Salt Hospital . Adults who presently have or previously had gallstone disease diagnosed by ultrasound, with or without thyroid disease confirmed or ruled out by obtaining TSH and T4 levels, were chosen using a non-probability sampling technique. Our final sample was 904. All of the data that was gathered and examined using statistical analysis.